2018
DOI: 10.1007/s11469-018-9899-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of “Colorful Life”: A Multi-Addiction Expressive Arts Intervention Program for Adolescents of Addicted Parents and Parents with Addiction

Abstract: This study evaluated an expressive arts intervention program (BColorful Life^) for adolescents with addicted parents and parents with addiction in Hong Kong. Different evaluation strategies were employed. Objective outcome evaluation adopting a one group pretest-posttest design showed positive changes in adolescents' (N = 43) beliefs about addiction. Both adolescents' and parents' (N = 21) psychosocial competencies were enhanced postintervention. Subjective outcome evaluation from both adolescent (N = 47) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Evaluation findings showed that after completion of the program, adolescents' beliefs about addiction significantly improved. At post-test, both adolescents and parents' psychosocial competencies were enhanced, and the participants expressed positive perceptions about the program content, implementers, and effectiveness of the program [55]. Notwithstanding these positive findings, no significant behavioral changes in the participants were identified.…”
Section: Prevention and Intervention Programs For Youth Gambling In H...mentioning
confidence: 94%
See 1 more Smart Citation
“…Evaluation findings showed that after completion of the program, adolescents' beliefs about addiction significantly improved. At post-test, both adolescents and parents' psychosocial competencies were enhanced, and the participants expressed positive perceptions about the program content, implementers, and effectiveness of the program [55]. Notwithstanding these positive findings, no significant behavioral changes in the participants were identified.…”
Section: Prevention and Intervention Programs For Youth Gambling In H...mentioning
confidence: 94%
“…The second program ("Colorful Life") is an intervention program based on multiaddiction syndrome model, positive youth development, and expressive arts approaches, designed for both addicted parents and their adolescent children [54]. The program was offered to 47 adolescents and 22 parents.…”
Section: Prevention and Intervention Programs For Youth Gambling In H...mentioning
confidence: 99%